Malaysian consumers’ willingness to choose Islamic mortgage products: An extension of the theory of interpersonal behaviour - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri (Emerald Group Publishing Ltd., 2016)
Purpose: The purpose of this paper is to understand consumers’ willingness to choose Islamic mortgage products as a way to help Islamic banks tap into the Islamic mortgage sector in Malaysia. Design/methodology/approach: Using the Theory of Interpersonal Behaviour as a point of departure, this study proposes a framework that examines factors influencing consumers’ willingness to choose Islamic mortgage products. A total of 282 usable surveys are obtained from customers of Islamic banks and the data were analysed using partial least squares. Findings: The results indicate that affect, social factors, and facilitating conditions influence willingness to choose Islamic mortgages. Besides these factors, the added factors, namely, perceived risk and perceived financial benefit, significantly influence consumers’ willingness to choose Islamic mortgages. Research limitations/implications: This study is confined to two public universities in Malaysia. Further testing of the proposed model across different population groups is necessary to determine the generalisability of this study’s findings. This study applies consumer factors such as affect, social factors, facilitating conditions, perceived risk and perceived financial benefit. Further testing on other factors is needed to expand the findings in this area. Practical implications: The results could help bank managers make improved decisions about the factors which they need to effectively market Islamic mortgage products. This study provides insights and guidance for bank managers to manage Islamic mortgage products. Originality/value: The main contribution of this paper is a proposed framework of consumers’ willingness to choose Islamic mortgage products which takes into account the key factors necessary to predict consumers’ demand.